Kebijakan Kua Medan Deli: Dampaknya Terhadap Peningkatan Kualitas Layanan Keagamaan di Masyarakat - Efendi, Rustam; Siregar, Idris; Zikraa; Affandi, Ahmad; Mahendra, Ihza; Nisak, Khairun (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article aims to analyze the policies implemented at the Office of Religious Affairs (KUA) in Medan Deli and their impact on improving the quality of religious services in the community. The research uses a qualitative approach with a case study at the KUA in Medan Deli, involving in-depth interviews with KUA staff and community members directly engaged in religious services. The findings reveal that the existing policies have positively contributed to the improvement of services, particularly in marriage services, religious guidance, and increased community participation. However, challenges remain in the consistent implementation of policies. The internship program for students has also proven to have a positive impact on enhancing the quality of services at the KUA in Medan Deli.